Recyclable polymer-bonded explosives enabled by thiol-cured disulfide-based epoxy vitrimers. (16th May 2023) - Chen, Mao; Duan, Shuyi; Zhou, Lin; Chen, Zhongtao; Zhang, Yinyu; Wu, Yeping; Zhu, Qing; Zhang, Kuibao; Zhao, Xiuli
Abstract: Polymer-bonded explosives (PBXs) that make up of high explosives and polymeric materials have been widely used as propellants, explosives and pyrotechnics in various industry. However, due to the cross-linked networks of polymers, the inflammable and toxic PBXs wastes that cannot be degraded and recycled are commonly burned or buried, leading to environmental pollution and economic loss. Due to the ultra-high sensitivity and high solid content of PBXs, it is a great challenge to achieve recyclable cross-linked PBXs. Herein, a thiol-cured disulfide-based epoxy vitrimer was prepared to bond high explosives of HMX, resulting in vitrimer-bonded explosives (VBXs). Due to the neutral and mild properties of disulfide epoxy monomers and thiol curing agents, the epoxy vitrimers exhibited good compatibility with the ultra-sensitive HMX. Meanwhile, intrinsic properties and dynamic properties of the epoxy vitrimers were both investigated. Moreover, the VBXs that consisted of 82 wt% HMX and 18 wt% epoxy vitrimers exhibited outstanding solvent resistance and excellent mechanical properties, while the compression strength was up to ∼35.1 MPa. Besides, the VBXs were successfully degraded by the neutral thiol solutions and the HMX was recycled from the VBXs non-destructively, which was confirmed by 13 C NMR. To the best of our knowledge, it is the first time to achieve recyclable PBXs relying on vitrimer materials, which will provide a new insight for the green development of energetic composites, while the thiol-cured disulfide-based epoxy vitrimer will have the potential for more other demanding applications. Graphical abstract: Image 1 Highlights: A thiol-cured disulfide-based epoxy vitrimer was prepared from disulfide epoxy monomers and thiol curing agents. The epoxy vitrimer was applied to bond high explosives of HMX, resulting in vitrimer-bonded explosives (VBXs). The VBXs containing 82% HMX and 18% epoxy vitrimers exhibited outstanding solvent resistance and mechanical properties. The VBXs were successfully degraded by the neutral thiol solutions and the HMX was recycled from the VBXs non-destructively.